2001
DOI: 10.1046/j.1462-5822.2001.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of EspF in host cell death induced by enteropathogenic Escherichia coli

Abstract: Enteropathogenic Escherichia coli (EPEC) causes diarrhoea in children in developing countries. Many EPEC genes involved in virulence are contained within the locus of enterocyte effacement (LEE), a large pathogenicity island. One of the genes at the far righthand end of the LEE encodes EspF, an EPEC secreted protein of unknown function. EspF, like the other Esps, is a substrate for secretion by the type III secretory system. Previous studies found that an espF mutant behaved as wild type in assays of adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
130
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 45 publications
7
130
1
3
Order By: Relevance
“…This was observed with several cell lines including epithelial HeLa cells and DU17 fibroblasts (data not shown). Similar observations were reported by Crane et al (2001). In that case, EPEC induced the detachment of T84 polarized epithelial cells.…”
Section: Epec Is Using Its Ttss To Induce the Detachment Of Infected supporting
confidence: 90%
See 3 more Smart Citations
“…This was observed with several cell lines including epithelial HeLa cells and DU17 fibroblasts (data not shown). Similar observations were reported by Crane et al (2001). In that case, EPEC induced the detachment of T84 polarized epithelial cells.…”
Section: Epec Is Using Its Ttss To Induce the Detachment Of Infected supporting
confidence: 90%
“…We showed that EPEC induced the detachment of all the examined cell lines including epithelial cell lines (HeLa, Caco2) and fibroblasts (DU17). Detachment of other epithelial cell lines including T84 was noticed by others but not quantified (Crane et al, 2001). We demonstrated that detachment of infected cells was initiated early after infection and was particularly dramatic in the DU17 fibroblast cell line.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…27). In addition, the espF mutant fails to induce apoptosis in host cells, another feature of the EPEC-host cell interaction (28). Application of EspF to the exterior of cells has no effect, but synthesis of EspF in transfected cells results in rapid cell death.…”
Section: Bacterial Polymorphismsmentioning
confidence: 99%